La réélection de Lula et la Gauche au Brésil - Adilar Cigolini; Francisco Mendonça; Irani dos Santos (EchoGéo)
Contrary to the forecasts, Lula was massively re-elected in 2006 with the support of the most underprivileged populations for which it implemented social measures in particular against the hunger, ethnic discrimination or violence towards the women. In its first mandate, it promoted the action of the State by founding the participative democracy on the topics of health, education, installation, the environment or the human rights, which the middle class also appreciated. Thanks to his charismatic personality and his modest origin, the people feel represented and is identified with him. Economically speaking, it nevertheless maintained the main trends of the preceding government and by the means of the negotiation, it reinforced the international and regional role (MERCOSUD) of Brazil. This shows that in Latin America, the politicians must from now on take into account the people to govern.